Evaluation of medication errors in nursing during the COVID-19 pandemic and their relationship with shift work at teaching hospitals: a cross-sectional study in Iran - Gilavand, Abdolreza; Jafarian, Negar; Zarea, Kourosh (Frontiers in Medicine, 2023)
Introduction: Medication errors in nursing negatively affect the quality of the provided health-treatment services and society's mentality about the health system, threatening the patient's life. Therefore, this study evaluates medication errors in nursing during the COVID-19 pandemic and their relationship with shift work at teaching hospitals. Materials and methods: All the nurses working at teaching hospitals affiliated with Ahvaz Jundishapur University of Medical Sciences (southwest of Iran) comprised the statistical population of this research (260 participants). Data were collected using three questionnaires: a demographic characteristics questionnaire, a medication error questionnaire, and the standard Circadian Type Inventory (CTI) for a normal physiological cycle. Results: At least one medication error was observed in 83.1% of nurses during their work span. A medication error was found in 36.2% of nurses during the COVID-19 pandemic (over the past year). Most medication errors (65.8%) occurred during the night shift. A significant relationship was detected between medication errors and shift work. Medicating one patient's drug to another (28.84%) and giving the wrong dose of drugs (27.69) were the most common types of medication errors. The utmost medication error was reported in emergency wards. The fear of reporting (with an average of 33.06) was the most important reason for not reporting medication errors (P < 0.01). Discussion and conclusion: Most nurses experienced a history of medication errors, which were increased by shift work and the COVID-19 pandemic. Necessary plans are recommended to reduce the fatigue and anxiety of nurses and prevent their burnout, particularly in critical situations. Efforts to identify risky areas, setting up reporting systems and error reduction strategies can help to develop preventive medicine. On the other hand, since the quality of people's lives is considered the standard of countries' superiority, by clarifying medical errors, a higher level of health, satisfaction and safety of patients will be provided.